Liquid LPG injection behavior in a spark ignition engine at idle state condition - Mustaffa, Norrizal; Fawzi, Mas; Amir Khalid, Amir Khalid; Norrizam Jaat, Norrizam Jaat; Tukiman, Mohd Mustaqim; Khairu Kamarudin, Khairu Kamarudin; Masrol, Shaiful Rizal; Esa, Mohd Faizal (2024)
LPG has emerged as an alternative fuel due to several reasons such as to establish the energy security for future usage. The usage of LPG in spark ignition engine has been around since few years ago. The LPG fuel injection technology has evolved from gas injection into liquid injection. Since the liquid phase injection is a latest technology, the present study aims to perform an analysis and comparison of LPG liquid phase injection and gasoline at idle state condition. The torque and performance curve were also been analyzed as an additional data. A four stroke 1.6L naturally aspirated engine was used for the experiment and few devices were attached to the engine in order to collect the required data. As summary, emissions of carbon based product of liquid phase LPG injection were found lower than gasoline and the combustion stability of LPG was observed in acceptable limit. Other than that, liquid phase LPG injection also capable to produced higher power output as compared to the gasoline.